Colloidal Cu/ZnO catalysts for the hydrogenation of carbon dioxide to methanol: investigating catalyst preparation and ligand effects - Pike, S; García-Trenco, A; White, E; Leung, A; Weiner, J; Shaffer, M; Williams, C (Royal Society of Chemistry, 2017)
The production of methanol from CO 2 hydrogenation is a promising potential route to a renewable liquid fuel and renewable energy vector. Herein, three distinct routes to make colloidal catalysts based on mixtures of Cu(0) and ZnO nanoparticles (NPs) and using low-temperature organometallic procedures are reported. The colloids are surface coordinated by a phosphinate ligand: dioctylphosphinate ([DOPA] - ), which delivers a high solubility in organic solvents. Further, the synthetic routes allow fine control of the ZnO:Cu and ligand loadings. The catalysts are prepared by mixing s mall NPs (2 nm) of either Cu(0) or air-stable Cu 2 O NPs with ZnO NPs (3 nm), or by the synthesis of Cu(0) in presence of ZnO NPs (ZnO: 2 nm, Cu: 6 nm). The resulting colloidal catalysts are applied in the liquid phase hydrogenation of CO 2 to methanol (210 °C, 50 bar, 3:1 molar ratio of CO 2 :H 2 ). The catalysts typically exhibit 3 times higher rates when compared to a heterogeneous Cu-ZnO-Al 2 O 3 commercial catalyst (21 vs. 7 mmol MeOH g CuZnO -1 h -1 ). The characterisation of the post-catalysis colloids show clear Cu/ZnO interfaces (HR-TEM), which are formed under reducing conditions, as well as differences in the Cu(0) NP size (from 3 to 7 nm) and nanoscale restructuring of the catalysts. The combination of characterisation and catalytic results indicate that the activity is mostly dictated by the Cu(0) particle size and ligand loading. Smaller Cu(0) NPs exhibited lower turnover frequency (TOF) values, whereas higher ligand loadings ([DOPA] - :(Cu + Zn) of 0.2-1.1) lead to smaller Cu(0) NPs and reduce the formation of Cu/ZnO interfaces. UV-vis spectroscopy reveals that the Cu(0) NPs are more stable to oxidation under air after catalysis than beforehand, potentially due to migration of ZnO onto the Cu surface whilst under catalytic conditions.